Efektivitas Penggunaan Alat Pengolah Air Limbah “SM” Terhadap Kualitas Fisik dan Kimia Air Limbah Laundry - Tri Marthy Mulyasari; Mela Firdaust (Buletin Keslingmas, 2025)
The rate of population growth every year follows the increase in the use of detergents. If the wastewater contains excessive detergents, it will cause pollution and disrupt the biota ecosystem in the waters. Fabric softeners and detergents are the main sources of laundry waste. Laundry wastewater treatment is necessary so that wastewater is safe to be disposed of into the environment. The study was conducted with the aim of analyzing the effectiveness of the use of SM wastewater treatment equipment on the physical and chemical quality of laundry wastewater. Pre-experimental research with a one shoot case study design. The research variables were TDS, odor, color, phosphate and COD. Replication was carried out 6 times. The research sample was in the form of laundry wastewater in the Baturraden District, Banyumas Regency, Indonesia. Data analysis was conducted using the paired T test. SM equipment can treat laundry wastewater as much as 960 liters/day. The organoleptic test of the physical quality of wastewater after treatment is still slightly fragrant and clear. The wastewater TDS of 349.17 ppm increased by 23.68% after treatment, with a p value of 0.055 indicating that the waste treatment equipment was not effective in reducing TDS. The COD of wastewater after treatment decreased by 54% with a p value of 0.005 indicating that the waste treatment device was effective in reducing COD. The phosphate content of wastewater after treatment decreased by 44.85% with a p value of 0.428, indicating that the waste treatment equipment was effective in reducing phosphate. The use of SM tools to treat laundry waste effectively lowers phosphate and COD, but increases TDS. Additional sedimentation time, and additional coagulation flocculation tanks are required to improve the performance of the SM tool.